218k views
14 votes
Please help me solve this

Please help me solve this-example-1

1 Answer

4 votes

Answer:

x = 24

Explanation:

using the rule of exponents


a^(m) ×
a^(n) =
a^((m +n))

consider left side


5^{(x)/(6) } ×
5^{(x)/(2) }

=
5^{(x)/(6) } ×
5^{(3x)/(6) }

=
5^{(4x)/(6) }

then


5^{(4x)/(6) } =
5^(16)

since the bases on both sides are equal, both 5 then equate exponents


(4x)/(6) = 16 ( multiply both sides by 6 )

4x = 96 ( divide both sides by 4 )

x = 24

User Nayab Siddiqui
by
4.8k points